Automatic forest fire monitoring system via IoT technology / Muhammad Firdaus Suhaimi - Suhaimi, Muhammad Firdaus (2024)
The forest may be impacted by unpredictable weather or weather changes, particularly when the surrounding weather or temperature appears to be extremely hot. The main crucial problem is to set crucial safety measures in place to avert disasters, smoke, and gas leakage detectors which highly helpful for the environment. The objective is to analyze the data collected by the temperature sensor, gas sensor and soil sensor to alert the current situation in the forest in a real-time. This report aims to design Smart Forest Fire Monitoring System Via IoT Technology using Arduino Microcontroller. In this project, main input that used are gas sensor, temperature sensor and soil sensor which determine the condition of the environment. As for the output, ESP8266 is used to simulate the LCD screen which to monitor the environment in real-time and the LED to alert the situation within the area of the environment that monitored. People can evaluate the system's capability to accurately detect fires, reduce false alarms, and send timely alerts to any important participants in the area by simulating the real-time data processing. As for the upcoming future work, the monitoring system's communication infrastructure can be upgraded by incorporating new technologies like satellite communications or wireless mesh networks to ensure dependable and timely data transmission from far away forest locations.